The Effect of Vitamin D Supplementation in Psoriasis: A Systematic Literature Review - Ulva, Maria; Yenti Sukarida; Mery Lisa Pratiwi (Open Access Indonesian Journal of Medical Reviews, 2023)
One of the key factors in the development of psoriasis is inflammation. In people with psoriasis, the immune system mistakenly attacks healthy skin cells, causing them to grow too quickly. This leads to the buildup of dead skin cells on the surface of the skin. Vitamin D can help to reduce inflammation by suppressing the production of pro-inflammatory cytokines. This study aimed to conduct a systematic review to explore the potential of vitamin D supplementation in psoriasis. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of vitamin D supplementation in psoriasis. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Vitamin D inhibits the inflammatory process in psoriasis by inhibiting the production of pro-inflammatory cytokines, activating anti-inflammatory, immune cells, and protecting cells from damage caused by inflammation.